Experimental and computational study of stresses on outdoor piping of domestic air conditioner / Loh Yin Kuan - Loh, Yin Kuan (2012)
Piping is a system of pipes used to transfer fluids from one location to another. Refrigerant piping system is used in the air-conditioner to transfer heat from one place to the other place by the refrigerant. One major requirement in refrigeration piping design is to provide adequate flexibility for absorbing the thermal expansion or contraction of the pipe. Piping system shall be designed to be free from high stress originated from thermal stress during operation to prevent product short life cycle and failure. Extensive researches and studies on the design parameters affecting the piping stress are required in order to achieve distinctive and economical piping system design. The current work is to study the effects of pipe wall thickness, temperature difference between pipe suction temperature and ambient temperature, and pipe length on piping stress. First of all, experimentations are performed to study the effects of these three parameters on pipe stress. Test result indicates that the thicker wall thickness does not reduce the thermal expansion or contraction stress. It only unfavorably increases the forces and moments in the pipe and consequently causes higher stress in adjacent pipe region. An increase in the temperature difference between pipe suction temperature and ambient temperature increases the thermal contraction stress due to higher degree of thermal contraction. Longer pipe length reduces the thermal contraction stress for the reason that it provides better flexibility for absorbing the thermal contraction. Finite element analysis is then used to predict the stress level of pipe in one of the test conditions and it is validated by the experimental result. The simulated stress result is below 16% in error compared to experimental test data. Subsequently, finite element methodology is employed to predict the effect of five different pipe lengths on stress. It can be observed from the simulation that the pipe stress reduces with increasing pipe length. This result is compatible with the test result and theory.